International finance regulation : the quest for financial stability - Ugeux, Georges (Hoboken : Wiley, 2014)
'As the global market expands, the need for international regulation becomes urgentEffective financial regulation inspires market confidence, stability, consumer protection, and a reduction in financial crime. But over the past fifty years, a number of crises have arisen and spread around the world, making global regulation essentially impossible. The last crisis was endogenous due to internal flaws in the management and the structure of the financial system. While individual nations have reformed domestic regulation, these combined measures are still insufficient to prevent financial crisis. Comprehensive crisis prevention can only be initiated by strategic international regulation. International Finance Regulation: The Quest for Financial Stability focuses on the inspirations behind regulation, and examines the risks and consequences of fragmentation on a global scale. Author Georges Ugeux has four decades of experience in the legal and economic aspects of international finance. Formerly in charge of the NYSE and foreign stock exchanges, regulators, and governments, Ugeux is uniquely positioned to provide recommendations and suggestions from the perspective of a top global authority. In the book, he explores international regulation with topics such as: Laws, regulations, and the risks stemming from overregulation The transformation of the U.S. market and the creation of the Eurozone Development of a global framework and the inadequacy of the banking system In-depth examination of Basel III, the Dodd-Frank Act, Glass-Steagall Act, and the Volcker Rule The book also contains case studies from real-world scenarios like Lehman, CDS, Greece, the London Whale, and Libor to illustrate the concepts presented. Finance consistently operates within an increasingly global paradigm, and an overarching regulation scheme is becoming more and more necessary for sustainable growth. International Finance Regulation: The Quest for Financial Stability presents an argument for collaboration toward a comprehensive global regulation strategy to reach financial stability'--
14: Was it a Global Crisis? The Asian Perspective Japan China India Assessing the Asian Risk -- 15: The Challenges of Global Regulation Regulation, Policies, and Politics Regulators and Sovereign Financing The ECB Supervision: The E.U. Governance Challenges The Risks of Regulatory Fragmentation Bank Resolution: The Legal Nightmare Basel III The Reemergence of Capital Markets Restructuring Finance Should Financial Communication Be Regulated? Should Financial Media Respect a Code of Conduct? Financial Education is Key -- 16: Regulation and Ethics Management Integrity Accountability Transparency is Key A Principled Regulatory System is Needed Doing the Right Thing Conclusion: What Can We Expect?
Machine generated contents note: Preface Is Finance In a Stage of Permanent Crisis? Global Markets Are Interconnected Regulating Finance in a World in Crisis A Web of Institutional Complexity Will Global Financial Regulation become Lex America? Applying Global Regulatory Convergence Regulator and Regulated: The Infernal Couple Finance Cannot Be Left Unregulated Five Years after Lehman, Regulation Could Not Change the Culture A Culture of Outlaws I Will Never Give Up Notes Chapter 1: The Multiple Objectives of Financial Regulation1 Stop (Ab)using Taxpayer Money Protect Retail and Small Investors and Depositors Ensure Transparency of Markets and Institutions Implement a Truly Risk Adjusted Remuneration System Protect Deposits from Trading Notes Chapter 2: A Quarter Century of Banking Crises and the Evolution of Financial Institutions Banking Crises are No Exactly a Recent Phenomenon The Two Main Emerging Market Crises The Subprime Crisis The Lehman Crisis The European Sovereign Debt Crisis The European Banking Crisis The Libor Manipulation Will the Foreign Exchange Market Be Next? Notes Chapter 3: The Lessons of the Recent Financial Crises: The Explosion of Balance Sheets The Structural Overbanking of Europe The Lack of Transparency of the Derivative Markets The Emergence of the Credit Default Swaps (CDS) Market The Regulatory Landscape Is Not Global, But Largely National Notes Chapter 4: Global Financial Regulation: The Institutional Complexities The Group of Twenty (G20) The Financial Stability Board (FSB) The Bank for International Settlements (BIS) and the Basel Committee (BCBS) The International Monetary Fund (IMF) The International Organization of Securities Commissions (IOSCO) The International Accounting Standard Board (IASB) The International Association of Insurance Supervisors (IAIS) Notes Chapter 5: Capital Adequacy, Liquidity and Leverage Ratios: Sailing Towards the Basel III Rules Part I: Capital Adequacy Part II: Liquidity Part III: Leverage Notes Chapter 6: Assessing Likely Impacts of Regulation on the Real Economy Notes Chapter 7: Regulating the Derivatives Market The Origin of the Derivatives Market The Size of the Derivatives Markets U.S. Regulation: Dodd Frank Act European Market Infrastructure Regulation (EMIR) The Transatlantic Divergences Short Selling is a Form of Derivative The JP Morgan Chase London Trading Losses Notes Chapter 8: The Structure of Banking: How Many Degrees of Separation? Systemically Important Financial Institutions (SIFI) The Universal Banking Model Separation Models United Kingdom United States European Union Switzerland The Volcker Rule and Proprietary Trading 15 Too Big To Fail (TBTF): Is Size the Problem? Prohibit the Trading of Commodities by Banks Notes Chapter 9: Banking Resolution and Recovery Moral Hazard Can the Bail-In Concept Avoid Taxpayers' Bailout? Lessons from the Financial Crisis Living Will or How Banks Want to Be Treated if They Are Close to Collapsing United States The Citi Recovery Plan The Role of the Federal Deposit Insurance Corporation in the United States Sheila Bair Was the Chair of FDIC during the Financial Crisis United Kingdom European Banking Resolution and Recovery Directive Regulatory Technical Standards Can Resolution Rules be Effective? An Impossible European Institutional Challenge Who Will Decide to Put Companies Under Resolution Surveillance? Notes Chapter 10: Banking and Shadow Banking Hedge Funds United States Europe Other Types of Shadow Banking Capital Markets and Securitization Notes Chapter 11: Rating Agencies and Auditors Part I: The Rating Agencies Part II: External Auditors Part III: The Limits of Accountability Notes Chapter 12: Central Banks As Lenders of Last Resort Have a Conflict of Interest with Their Regulatory Role Financial Stability The United States: Quantitative Easing European Central Bank: The Long Term Revolving Operations (LTRO) The United Kingdom Japan and Abenomics Are Central Banks Balance Sheets Eternally Expandable? Have they becomeHedge Funds? Is This Novation of Central Banks Legitimate or Legal? Notes Chapter 13: Financial Institutions Governance (or Lack Thereof) Risk Management The Dysfunctional Boards of Directors Should the Chairperson Also be the CEO? Remuneration and Risks Personal or Institutional Accountability Notes Chapter 14: Was it a Global Crisis? The Asian Perspective Japan China India Assessing the Asian Risk Notes Chapter 15: The Challenges of Global Regulation Regulation, Policies, and Politics Regulators and Sovereign Financing The ECB Supervision: The E.U. Governance Challenges The Risks of Regulatory Fragmentation Bank Resolution: The Legal Nightmare Basel III The Reemergence of Capital Markets Restructuring Finance Should Financial Communication Be Regulated? Should Financial Media Respect a Code of Conduct? Financial Education is Key Notes Chapter 16: Regulation and Ethics Management Integrity Accountability Transparency is Key A Principled Regulatory System is Needed Doing the Right Thing Notes Conclusion: What Can We Expect? A few books I read and found helpful ... About the Author Index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: International finance; International finance -- Law and legislation; Banks and banking; Electronic books; Electronic books